S.A. Beznosyuk as the Founder and Leader of a New Direction of Quantum Field Chemistry in Subatomic Quantum Nanotechnologies of Materials - Zhukovsky, M.S.; Maslova, O.A. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article highlights the creative path of S.A. Beznosyuk, an outstanding physico-chemist, who celebrates his 70th anniversary in 2023. The main stages of his career and significant events of his scientific creativity are presented here. The contribution of Professor S.A. Beznosyuk to the establishment and development of two scientific schools, namely quantum field chemistry of the condensed state at the Karaganda Buketov University and subatomic quantum nanotechnology of materials at Altai State University is shown.